EP384 Laparoscopic radical hysterectomy with consequent transvaginal closure of vaginal cuff – results of a retrospective analysis of a prospective collected multicentre database. (1st November 2019) - Köhler, C; Hertel, H; Herrmann, J; Marnitz, S; Mallmann, P; Favero, G; Plaikner, A; Martus, P; Gajda, M; Schneider, A
Abstract : Introduction/Background: Laparoscopic/robotic radical hysterectomy (RH) has been considered oncologically adequate to open RH for patients with early cervical cancer. However, a recent prospective randomised trial (LACC) demonstrates significant inferiority of minimally-invasive approach. Thereupon we have updated our prospective database of combined laparoscopic-vaginal RH with respect to oncologic outcome. Methodology: Between 1994 and 2018 1952 consecutive patients with invasive cervical cancer have been treated using minimally-invasive surgery at the Universities of Jena, Charité Berlin (Campus CCM and CBF) and Cologne and Asklepios Clinic Hamburg. 389 patients with inclusion criteria identical to LACC trial were identified. In contrast to laparoscopic/robotic technique used in LACC trial all patients in our cohort underwent combined transvaginal-laparoscopic approach that does not use any uterine manipulator and comprises creation of a tumor-adapted vaginal cuff by transvaginal approach. Results: Initial FIGO stage was IA1 LVSI+, IA2 and IB1 in 32 (8%), 43 (11%) and 314 (81%) respectively, and histology was squamous cell cancer in 263 (68%), adenocarcinoma in 117 (30%) and adenosquamous tumor in 9 (2%). LVSI was confirmed in 106 patients (27%). Median number of harvested lymph nodes was 24 (2–86). Lymph nodes were tumor-free in 379 (97%) of patients. Following radical hysterectomy 71 (18%) of patients underwent adjuvant chemoradiation (CRT) or radiation (RT). After a median follow up of 99 (1–288) months 3, 4.5 and 10-ys DFS were 96.8%, 95.8%, 93.1% and 3, 4.5 and 10-year OS were 98.5%, 97.8%, 95.8%, respectively. Recurrences were diagnosed in 50% (n=10) loco-regional. Interestingly, 9/20 recurrences occurred later than 39 months following surgery. Conclusion: Combined laparoscopic-vaginal technique for RH with consequent avoidance of possible spillage and manipulation of tumor cells provides excellent oncologic outcome for patients with early cervical cancer. Our retrospective data suggest that laparoscopic-vaginal surgery respecting laparoscopic oncologic hygiene is oncologic safe and should be validated in further randomised trials. Disclosure: Nothing to disclose.